2014
DOI: 10.1021/bm500939x
|View full text |Cite
|
Sign up to set email alerts
|

Biocomposites of Nanofibrillated Cellulose, Polypyrrole, and Silver Nanoparticles with Electroconductive and Antimicrobial Properties

Abstract: In this work, flexible and free-standing composite films of nanofibrillated cellulose/polypyrrole (NFC/PPy) and NFC/PPy-silver nanoparticles (NFC/PPy-Ag) have been synthesized for the first time via in situ one-step chemical polymerization and applied in potential biomedical applications. Incorporation of NFC into PPy significantly improved its film formation ability resulting in composite materials with good mechanical and electrical properties. It is shown that the NFC/PPy-Ag composite films have strong inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 105 publications
(47 citation statements)
references
References 63 publications
1
44
1
1
Order By: Relevance
“…The N 2 ‐pNPGC 4 exhibited one‐step weight loss ranging from 170 to 310 °C and the maximum differential weight loss occurred at 250 °C. This value was slightly lower than that of pure pNPGC . N‐pNPGC 3 showed weight loss at 240–350 °C and their maximum differential weight loss was about 50 °C higher than that of N 2 ‐pNPGC 4 .…”
Section: Resultsmentioning
confidence: 93%
“…The N 2 ‐pNPGC 4 exhibited one‐step weight loss ranging from 170 to 310 °C and the maximum differential weight loss occurred at 250 °C. This value was slightly lower than that of pure pNPGC . N‐pNPGC 3 showed weight loss at 240–350 °C and their maximum differential weight loss was about 50 °C higher than that of N 2 ‐pNPGC 4 .…”
Section: Resultsmentioning
confidence: 93%
“…By incorporating copper (Cu) or Ag nanoparticles, anti-microbial films or membranes from regenerated cellulose, bacterial cellulose, or cellulose derivatives can be prepared (Berndt et al 2013;Drogat et al 2010;Jia et al 2012;Xu et al 2013;Zheng et al 2014). Bober et al reported the preparation of antimicrobial biocomposites using nanofibrillated cellulose, polypyrrole, and Ag nanoparticles, which strongly inhibited the growth of Gram-positive bacteria, such as S. aureus (Bober et al 2014). By incorporating luminescent and fluorescent Ag nanoclusters into the nanocomposites of nanofibrillated cellulose, fluorescent and antibacterial films were obtained (Diez et al 2011).…”
Section: Non-adhesive Surfacesmentioning
confidence: 99%
“…In addition, using silver nitrate as a direct oxidant of Py monomer for the production of conducting PPy/Ag composites has been reported . PPy/Ag composites loading on oxide metal, fabric cotton, cellulose, or polymer membrane has been discussed. In this single‐step process, reduction of Ag + to the metal on the PPy surface was found to be caused by the redox reaction between the positively charged and growing Py chains.…”
Section: Introductionmentioning
confidence: 99%